Neoadjuvant rectal score as individual-level surrogate for disease-free survival in rectal cancer in the CAO/ARO/AIO-04 randomized phase III trial - Fokas, Emmanouil; Hofheinz, Ralf-Dieter (Annals of oncology, 2018)
Background - Surrogate end points in rectal cancer after preoperative chemoradiation are lacking as their statistical validation poses major challenges, including confirmation based on large phase III trials. We examined the prognostic role and individual-level surrogacy of neoadjuvant rectal (NAR) score that incorporates weighted cT, ypT and ypN categories for disease-free survival (DFS) in 1191 patients with rectal carcinoma treated within the CAO/ARO/AIO-04 phase III trial. - Patients and methods - Cox regression models adjusted for treatment arm, resection status, and NAR score were used in multivariable analysis. The four Prentice criteria (PC1-4) were used to assess individual-level surrogacy of NAR for DFS. - Results - After a median follow-up of 50months, the addition of oxaliplatin to fluorouracil-based chemoradiotherapy (CRT) significantly improved 3-year DFS [75.9% (95% confidence interval [CI] 72.30% to 79.50%) versus 71.3% (95% CI 67.60% to 74.90%); P=0.034; PC 1) and resulted in a shift toward lower NAR groups (P=0.034, PC 2) compared with fluorouracil-only CRT. The 3-year DFS was 91.7% (95% CI 88.2% to 95.2%), 81.8% (95% CI 78.4% to 85.1%), and 58.1% (95% CI 52.4% to 63.9%) for low, intermediate, and high NAR score, respectively (P<0.001; PC 3). NAR score remained an independent prognostic factor for DFS [low versus high NAR: hazard ratio (HR) 4.670; 95% CI 3.106-7.020; P<0.001; low versus intermediate NAR: HR 1.971; 95% CI 1.303-2.98; P=0.001] in multivariable analysis. Notwithstanding the inherent methodological difficulty in interpretation of PC 4 to establish surrogacy, the treatment effect on DFS was captured by NAR, supporting satisfaction of individual-level PC 4. - Conclusion - Our study validates the prognostic role and individual-level surrogacy of NAR score for DFS within a large randomized phase III trial. NAR score could help oncologists to speed up response-adapted therapeutic decision, and further large phase III trial data sets should aim to confirm trial-level surrogacy.
Gesehen am 20.10.2020